Pengaruh Tingkat Literasi Mahasiswa UIN Banten Mengenai Bank Syariah Terhadap Minat Menabung di Bank Syariah - Fairuz Salma, Tazkiya; Saputra, Rama; Fadhilah, Serliani; Hidayat, Wahyu; Saraswati, Henny (STAI Denpasar Bali, 2023)
Islamic banks are one of the many types of banks that implement sharia principles in their operational activities. Islamic banks play an important role in supporting economic and financial growth in Indonesia, and have become an alternative for people to save and manage their money. However, there are still many Banten UIN students who do not know about Islamic banking and how it works. The level of financial and banking literacy within the scope of UIN Banten students is an important factor that has the potential to influence their interest in saving money in Islamic banks. A low level of financial and banking literacy can make students not have adequate insight into products and services of Islamic banks, thus hindering their interest in saving at the bank. Therefore, this research is aimed at examining the effect of the literacy level of UIN Banten students regarding Islamic banks on their interest in saving in Islamic banks. This research is aimed at reviewing the level of Islamic financial literacy of students of Islamic economics and Islamic banking study programs and the influence of Islamic financial literacy levels on the use of Islamic banking products. Research categorized as quantitative research. Thus, increasing literacy around Islamic banking can strengthen the interest of UIN Banten students in saving money in Islamic banks. Keywords: Influence, literacy level, Islamic bank, interest in saving